Analysis methods and models of calculation of passenger correspondence - Білоус, Андрій Борисович; Демчук, Інна Андріївна (Eastern-European Journal of Enterprise Technologies, 2014)
Forming the correspondence matrix of passenger movements from a mathematical point of view is one of the most difficult tasks in researches related to significant structural or parametric changes of urban network traffic flows. The methods of forming the passenger correspondence matrices were considered in the paper, their advantages and disadvantages were identified. According to the analysis results, the basic requirements for models of calculating the volume of correspondences of residents’ movements in urban areas were established and using a fuzzy logic the models were properly selected. As for the models using the fuzzy logic theory it was found that one of the “weak” points is the correct definition of membership function parameters. For solving the problem of setting appropriate parameters of the membership functions and their correction during the model application, it was decided to use a mathematical tool of heuristics of genetic algorithms. The paper is an overview and is intended to organize information about currently developed methods and models of calculating the volume of movement correspondences in urban areas.